Understanding emotional teen dating violence perpetration through the Vulnerability-Stress-Adaptation model among pregnant and parenting Latinx adolescents - Choudhary, Sheetal (My University, 2026)
Teen dating violence (TDV) is a significant public health concern, particularly among Latinx pregnant and parenting adolescents. Despite this elevated risk, limited research has examined the multiple factors contributing to emotional TDV perpetration in this specific population using an integrated theoretical framework. The current study utilized the Vulnerability-Stress-Adaptation (VSA) model to examine how enduring vulnerabilities (interparental conflict and depressive symptoms), a stressor (emotional TDV victimization), and an adaptive process (constructive communication and negotiation skills) are associated with emotional TDV perpetration among Latinx pregnant and parenting adolescents. Data were drawn from the Strengthening Relationships/Strengthening Families (SRSF), a relationship education program implemented across eight high schools in Central Texas during the 2014-2015 academic year. The analytic sample consisted of 124 Latinx pregnant and parenting adolescents (including those whose partner was pregnant) aged 14 to 19 years. Participants completed self-report measures assessing emotional TDV perpetration and victimization, interparental conflict, depressive symptoms, and constructive communication and negotiation skills. Little’s MCAR test did not reject the assumption that missing data were missing completely at random, and Expectation-Maximization (EM) imputation was applied to retain the full sample of 124 participants. Hierarchical regression analyses were conducted to test the study hypotheses, with variables entered in three blocks aligned with the VSA framework: enduring vulnerabilities (Block 1), a stressor (Block 2), and an adaptive process (Block 3). Results indicated that the final model accounted for 37.8% of the variance in emotional TDV perpetration. In Block 1, enduring vulnerabilities accounted for 11.0% of the variance, with depressive symptoms emerging as a significant predictor. In Block 2, the addition of emotional TDV victimization significantly increased the explained variance by 25.9%, making it the strongest predictor of emotional TDV perpetration in the final model. In Block 3, constructive communication and negotiation skills did not significantly add to the model. In the final model, both depressive symptoms and emotional TDV victimization remained significant predictors of emotional TDV perpetration, while interparental conflict and constructive communication and negotiation skills did not. These findings provide partial support for the VSA model, showing a strong cross-sectional association between emotional TDV victimization and perpetration and underscoring the role of depressive symptoms as a key vulnerability factor. The findings have important theoretical and practical implications. Theoretically, this study extends the VSA model to a novel population of Latinx pregnant and parenting adolescents, reflecting its applicability beyond traditional marital research. Practically, the results emphasize the need for relationship education programs and clinical interventions that address mental health, particularly depressive symptoms, alongside teen dating violence prevention efforts. Findings also point to the importance of culturally tailored interventions for Latinx pregnant and parenting adolescents that address the strong co-occurrence of victimization and perpetration and integrate trauma-informed approaches. Limitations of the study include the use of cross-sectional secondary data, self-report measures, and a regional sample, which limit causal inferences and generalizability. Future research should employ longitudinal designs, examine additional cultural and contextual factors, and explore protective factors that may buffer the effects of vulnerabilities and stressors on emotional TDV perpetration in this population. Keywords: Latinx adolescents, perpetration, pregnant and parenting youth, teen dating violence, victimization, Vulnerability-Stress-Adaptation model
Keywords: Latinx adolescents; pregnant and parenting youth; teen dating violence; Vulnerability-Stress-Adaptation model; perpetration; victimization